Long Non-Coding RNA 691 Regulated PTEN/PI3K/AKT Signaling Pathway in Osteosarcoma Through ﻿miRNA-9-5p - Yao, Pengju (Onco Targets Ther, 2020)
BACKGROUND: Large amounts of researches indicate that non-coding RNAs play a crucial role in many malignancies. However, the potential mechanisms of non-coding RNAs involved in osteosarcoma tumorigenesis remain elusive. MATERIALS AND METHODS: The expression of long non-protein coding RNA 691 (lncRNA 691) in cell lines and paired osteosarcoma tissues was compared by qRT-PCR assay. Then, we explored the tumor suppressor function of lncRNA 691 with MTS and colony formation assay. Flow cytometry results showed lncRNA 691 can enhance cell apoptosis. Then, we predicted and verified the negative regulation relationship with miRNA and the miRNA’s target gene. Lastly, we revealed the tumorigenesis function of lncRNA-691/miRNA/target gene axis in osteosarcoma. RESULTS: In our study, we disclosed that lncRNA 691 had low expression levels in osteosarcoma cell lines and tissues. Overexpression of lncRNA 691 could suppress the cell proliferation and induce cell apoptosis in MG-63 cell line. Then, bioinformatics analyses were performed and miR-9-5p was found to negatively regulate the lncRNA 691 expression and promote the osteosarcoma tumorigenesis in vitro. PTEN was predicted as the target gene of miR-9-5p. Luciferase reporter assay and RIP assay demonstrated the regulatory network of lncRNA 691/miR-9-5p/PTEN. We revealed that PTEN was downregulated by the overexpression of miR-9-5p and upregulated by the overexpression of lncRNA 691. At last, the apoptosis﻿-associated protein of the lncRNA 691/miR-9-5p/PTEN/PI3K/AKT was further demonstrated. CONCLUSION: LncRNA 691/miR-9-5p could regulate the tumorigenesis by regulating the PTEN/PI3K/AKT signal pathway in osteosarcoma.